Clinical Observations of the Effectiveness of the Masquelet Induced Membrane Technique in the Treatment of Critical Long-Bone Defects of the Lower and Upper Extremities - Kamil Kołodziejczyk; Aleksander Ropielewski; Rafał Garlewicz; Marcin Złotorowicz; Jarosław Czubak (Medicina)
Background and Objectives: Successful treatment of severe trauma and fractures of the long bones with successful healing and bone union is still a significant challenge for surgeons. Unfortunately, up to 10% of long-bone fractures develop bone healing disorders. The aim of this study was to evaluate the results of treating bone defects with different etiologies in the upper and lower extremities using the induced membrane technique. Materials and Methods: We prospectively evaluated the radiological and clinical outcomes of 45 patients with severe bone defects treated with the induced membrane technique during the period from May 2021 to October 2023. The time to bone defect regeneration, size of the bone defect, and the cost of treatment were evaluated. Functional outcomes were assessed using the Disabilities of the Arm Shoulder and Hand (DASH) scale, SF-36, and the Lower Limb Functional Index (LLFI). Results: The mean follow-up time was 31 months (12–35). There were 20 patients with upper extremity bone defects and 25 with lower extremity bone defects. The mean defect length was 7.9 cm for the upper extremity (3.5–18) and 5.3 cm for the lower extremity (3–11). The mean times to achieve bone union and remodeling were 6.0 months (3–12) and 9 months (3–13) for the upper and lower limbs, respectively. Clinical evaluation at the end of treatment (achieving bone union) showed statistically significant improvements in the DASH, SF-36, and LLFI scales for pre- and postoperative outcomes. There was no statistical significance in the SF-36 clinical scale scores after surgical treatment compared to reconstructive treatment of upper and lower extremity bone defects. Results: The presented reconstructive approach to the treatment of bone defects and healing disorders and extensive analysis demonstrate the effectiveness of the induced membrane technique in a short follow-up period, with a relatively high level of patient comfort and good clinical results in the treatment of severe bone defects with particularly infectious etiologies.